2022
DOI: 10.25122/jml-2021-0384
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ knowledge, practice, and attitudes toward vitamin D deficiency among children in the Qassim region, Kingdom of Saudi Arabia

Abstract: Vitamin D comes in two forms: ergocalciferol (D2) and cholecalciferol (D3). This study aimed to assess mothers' knowledge, attitudes, and practices toward vitamin D deficiency among children. We collected data using a self-administered online questionnaire to gather information about the characteristics, knowledge, attitudes, and reported practices of 800 Saudi Arabian mothers regarding vitamin D deficiency. The mean age of participants was 31.2±4.76, and 8% had a university education. When it came to househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Depending on the main sources of vitamin D, the biggest answer (43%) identified by mothers was the option all above (sun, food, and supplements), (36.5%) answered from sun, (8.5%) from supplements, and (7%) from food. These results are similar to a study in the Saudi Kingdom 2017 and Cairo 2020 found that the majority of mothers correctly identified the sun as a source of vitamin D. (Bassam and Abd-Elmageed, 2022;Soliman et. al., 2020).…”
Section: Knowledge Partsupporting
confidence: 88%
“…Depending on the main sources of vitamin D, the biggest answer (43%) identified by mothers was the option all above (sun, food, and supplements), (36.5%) answered from sun, (8.5%) from supplements, and (7%) from food. These results are similar to a study in the Saudi Kingdom 2017 and Cairo 2020 found that the majority of mothers correctly identified the sun as a source of vitamin D. (Bassam and Abd-Elmageed, 2022;Soliman et. al., 2020).…”
Section: Knowledge Partsupporting
confidence: 88%